The role of thioredoxin in the regulation of cellular processes by S-nitrosylation - Sengupta, Rajib; Holmgren, Arne (Biochimica et biophysica acta, 2012)
S-nitrosylation (or S-nitrosation) by Nitric Oxide (NO), i.e., the covalent attachment of a NO group to a cysteine thiol and formation of S-nitrosothiols (R-S-N=O or RSNO), has emerged as an important feature of NO biology and pathobiology. Many NO-related biological functions have been directly associated with the S-nitrosothiols and a considerable number of S-nitrosylated proteins have been identified which can positively or negatively regulate various cellular processes including signaling and metabolic pathways. Taking account of the recent progress in the field of research, this review focuses on the regulation of cellular processes by S-nitrosylation and Trx-mediated cellular homeostasis of S-nitrosothiols. Thioredoxin (Trx) system in mammalian cells utilizes thiol and selenol groups to maintain a reducing intracellular environment to combat oxidative/nitrosative stress. Reduced glutathione (GSH) and Trx system perform the major role in denitrosylation of S-nitrosylated proteins. However, under certain conditions, oxidized form of mammalian Trx can be S-nitrosylated and then it can trans-S-nitrosylate target proteins, such as caspase 3. Investigations on the role of thioredoxin system in relation to biologically relevant RSNOs, their functions, and the mechanisms of S-denitrosylation facilitate the development of drugs and therapies. This article is part of a Special Issue entitled Regulation of Cellular Processes. ► S-nitrosylation is an important feature of NO biology and pathobiology. ► Many S-nitrosylated proteins regulate various cellular processes. ► Thioredoxin system plays an important role to combat oxidative/nitrosative stress. ► GSH and Trx system perform the major role in denitrosylation of RSNOs.